2019
DOI: 10.1111/jace.16391
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of rGO/AgCl QDs and its enhanced photoelectrocatalytic performance for the degradation of Tetracycline

Abstract: A novel rGO/AgCl QDs composites have been obtained by an ultrasonic‐assisted method for the first time. Photoelectrocatalytic (PEC) performances of the obtained samples were studied by the degradation of 20 mg/L Tetracycline (TC) under visible light irradiation with an applied bias potential of 1.5 V (vs Ag/AgCl). Degradation of TC by different processes including Photocatalysis (PC), Electrocatalysis (EC), and PEC was compared, and the effect of different bias potential on the PEC degradation of TC was discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…It can be found that all the diffraction peaks of the pristine AgCl were well matched to the cubic phase AgCl (JCPDS No. 02-0848) (Kadeer et al 2019). The diffraction peaks of single AgBr were also well matched to the cubic AgBr (JCPDS No.…”
Section: Characterization Of As-prepared Samplesmentioning
confidence: 63%
See 1 more Smart Citation
“…It can be found that all the diffraction peaks of the pristine AgCl were well matched to the cubic phase AgCl (JCPDS No. 02-0848) (Kadeer et al 2019). The diffraction peaks of single AgBr were also well matched to the cubic AgBr (JCPDS No.…”
Section: Characterization Of As-prepared Samplesmentioning
confidence: 63%
“…Ciprofloxacin (CIP), as a typical secondgeneration fluoroquinolone antibiotic with broad antimicrobial activity and good oral performance, had been widely used in human and veterinary medicine (Škorić et al 2013). However, antibiotics like CIP can be metabolized and absorbed partially when it enters human or animal body, and the remained is mainly discharged in the form of drugs, which are abundant in the environment (Kadeer et al 2019). Water contaminated by antibiotics such as CIP can cause bacterial resistance by inducing gene exchange, which seriously threatens human health and the whole ecosystem (Sengeløv et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…16 Advanced oxidation processes (AOPs) with high chemical stability and/or low biodegradability produce very active radicals at near ambient temperature and pressure and are considered as a powerful technology for the treatment of tetracycline from organic wastewaters into nontoxic products of CO 2 and H 2 O. 17,18 AOPs are environmentally friendly methods including wet oxidation, 19 photochemical oxidation, 20 electrochemical oxidation, 21 photoelectrochemical oxidation, 22 Fenton oxidation, 23 and photo-Fenton oxidation. 24 AOPs possess common features of the strong standard reduction potential, high bimolecular reaction rate constants, and nonselective reactivity of active radicals, which are beneficial to the rapid and high-efficiency degradation of organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the excellent conductivity of RGO is beneficial to accelerate the transfer of photogenerated electrons from photocatalysts to the surface of RGO, which could promote the separation of photogenerated electronhole pairs. 30,31 On the other hand, RGO could provide more active sites to adsorb more organic pollutant due to its high specific surface area. 32,33 For example, Reheman et al had prepared the RGO/Ag 3 PO 4 quantum dots (QDs) via a facile one-step sonochemical method, and the composite exhibited the improved photocatalytic performance for the removal of methylene blue (MB).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, reduced graphene oxide (RGO) is deemed to be an ideal supporting material to enhance the photocatalytic activity of Ag 3 VO 4 ‐based materials. On the one hand, the excellent conductivity of RGO is beneficial to accelerate the transfer of photogenerated electrons from photocatalysts to the surface of RGO, which could promote the separation of photogenerated electron‐hole pairs 30,31 . On the other hand, RGO could provide more active sites to adsorb more organic pollutant due to its high specific surface area 32,33 .…”
Section: Introductionmentioning
confidence: 99%